2009
DOI: 10.1108/09513570910945697
|View full text |Cite
|
Sign up to set email alerts
|

Management accounting in less developed countries: what is known and needs knowing

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
412
3
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 251 publications
(434 citation statements)
references
References 132 publications
(145 reference statements)
12
412
3
7
Order By: Relevance
“…While we do not wish to claim that the processual model will be applicable to all NPM-related cost management reforms, nevertheless, regressive outcomes are always a possibility, especially in the structural conditions where many public sector organisations operate in less developed countries. Previous studies have demonstrated similar structural conditions for NPM in poorer countries (Allawattagee et al, 2007;Hopper et al, 2009). In many of these cases, NPM reforms are brought about by private sector ideals of cost management and are championed by private sector change agents (Wickramasinghe and Hopper, 2005).…”
Section: Discussion and Concluding Remarksmentioning
confidence: 91%
See 4 more Smart Citations
“…While we do not wish to claim that the processual model will be applicable to all NPM-related cost management reforms, nevertheless, regressive outcomes are always a possibility, especially in the structural conditions where many public sector organisations operate in less developed countries. Previous studies have demonstrated similar structural conditions for NPM in poorer countries (Allawattagee et al, 2007;Hopper et al, 2009). In many of these cases, NPM reforms are brought about by private sector ideals of cost management and are championed by private sector change agents (Wickramasinghe and Hopper, 2005).…”
Section: Discussion and Concluding Remarksmentioning
confidence: 91%
“…Most of these shifts in policy are often a function of international politics and of the economic dependence of these countries on economically stronger nations (ibid). This political and economic context has had a direct bearing on the management accounting and control practices of public sector organisations in less developed countries (Hopper et al, 2009). First, in most of these public sector organisations, 'bureaucratic' management accounting and controls were in place to enable the state to make rational decisions about resource allocations.…”
Section: Npm Management Controls and Outcomesmentioning
confidence: 99%
See 3 more Smart Citations